1997
DOI: 10.1046/j.1365-2796.1997.74880000.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of pulmonary embolism: uncertainties and implications for treatment – a debate

Abstract: Abstract. Egermayer P, Town GI (The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…As technology improves, detection of increasingly smaller emboli is becoming possible. But instead of clarifying the need for treatment, their detection raises further questions: previously undetected emboli may have remained stable or self-resolved [79][80][81][82], so should they be treated with anticoagulant therapy, which carries a risk of bleeding [83] and increases economic cost? In this study, we have assessed the potential impact of subsegmental emboli on perfusion.…”
Section: (C) Subsegmental Embolismmentioning
confidence: 99%
See 1 more Smart Citation
“…As technology improves, detection of increasingly smaller emboli is becoming possible. But instead of clarifying the need for treatment, their detection raises further questions: previously undetected emboli may have remained stable or self-resolved [79][80][81][82], so should they be treated with anticoagulant therapy, which carries a risk of bleeding [83] and increases economic cost? In this study, we have assessed the potential impact of subsegmental emboli on perfusion.…”
Section: (C) Subsegmental Embolismmentioning
confidence: 99%
“…The long-term contribution to human health is, therefore, to pinpoint the characteristics of PE that are most worrisome, hence defining a patient that should be monitored more carefully, and conversely identifying the groups of patients for whom the risks associated with anticoagulant therapy are likely to outweigh the benefits [81,88]. This study will provide an important new approach to understand lung perfusion that will be equally applicable to studying alterations to perfusion and gas exchange in other respiratory diseases, particularly those for which PH is a component.…”
Section: (E) the Contribution Of Modelling Studies To Understanding Dmentioning
confidence: 99%
“…However, the clinical relevance of these small PEs is a matter of controversy, with some authors arguing that anticoagulation may be safely withheld in this setting [19,21]. Actually, in a large population of in-patients in whom PE had been excluded by CT pulmonary angiography (involving single-and multidetector row CT scans) without further work-up, KRUIP et al [20] have recently observed a 3-month risk of VTE of 4%.…”
Section: In-patient Diagnosis Of Pementioning
confidence: 99%
“…Major occlusion of the pulmonary arteries in association with chronic PH is estimated to occur in between 0.1±0.4% of autopsies [6,7]. By comparison evidence of recent or old pulmonary embolism (PE) may be found in between 60±90% of all autopsy cases [8].…”
mentioning
confidence: 99%